Optimizing Sports Training Lessons by Using the Led System for Beginner Basketball Groups - Adrian PAȘCAN; Cosmin MOCA (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae)
Optimizing sports training lessons by using the LED system for beginner basketball groups. Objectives. This paper proposes the introduction into the training plan of the beginner basketball groups of some modern means, namely led systems for the development of reaction speed by making decisions to visual signals. The main purpose of this paper is to study the effects of this approach on the U13 players of the CSS Gheorgheni basketball team. Materials and methods: The subjects of the experiment were the athletes of the beginner basketball group born in 2010-2011, namely 16 girls. Initial tests were applied, then the players were subjected to specific training by applying some modern means, and at the end the same tests were applied again. Results: At the first test on execution speed, we notice that all the athletes managed to improve their results. From the point of view of mistakes, also in this test, we notice that almost all the participants in the experiment improved their performance, three of them managing not to make any mistakes. In the throwing test, they all improved their performance. In the combined test (changes of direction and throwing in the basket) 7 athletes finished the route without any mistakes, 7 girls improved their performance, and 2 girls had the same number of mistakes. Conclusions: based on the results obtained, we can say with certainty that by using exercises based on an LED system for the development of reaction speed by making decisions to visual signals throughout the season, the performance of the sportswomen under research has improved.